An Analysis Of Students’ Anxiety On English Speaking At The First Year Students Of English Department In Muhammadiyah University Of Sumatera Barat - Novianti, Widya; Syandri, Gusmaizal; Sari, Mezia Kemala (FKIP UMSB, 2025)
The purposes of this research are to find out the factors that cause students’ anxiety, the types of student’s anxiety in speaking English and the alternative solutions to overcome student’s anxiety based on student’s perspective at the first year students of English Department in Muhammadiyah University of Sumatera Barat. This research is descriptive-qualitative research. The participants are 10 students who experienced anxiety in the class at first year students of English Department in Muhammadiyah University of Sumatera Barat. The data were taken from the results of open-ended questionnaire and the answers of interview. The results of this research showe that there are 5 factors that cause students’ anxiety in English speaking. The most dominant factors is Lack of Vocabularies, Then the others factors such as Fear of Making Mistakes, Lack of Confidence, Worry about Friends/Classmates Point of View and Types of Task that was Given by the Lecturer have also found. From these factors then three types of anxiety have been categorized. The most common type is Communication Apprehension, then Fear of Negative Evaluation and the least is Test Anxiety. Additionnally 3 alternative solutions to overcome students’ anxiety based on students’ perspective was found out. Firstly is Increase Self Confidence, secondly is Study Hard, and lastly is the Student should have Positive Mindset. Keywords : Speaking, Anxiety.